Mengurai Permasalahan Hukum Terkait Transaksi Keuangan dalam Pencucian Uang - Lisanawati, Go (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2023)
This study aims to analyze the consistency and effectiveness of the formulation of suspicious financial transactions in legal regulations related to money laundering from the law to the implementing rules. The issue discussed was related to the proposal to reformulate the definition of financial transactions as part of suspicious activity. The urgency of debating this issue is to avoid inconsistencies in the meaning and implementation of indicators of these financial transactions to provide effective prevention for all parties responsible for the anti-money laundering regime. This research uses normative juridical law research, with the object of research in the form of a positive legal inventory. The findings in this study are that efforts to reformulate the formulation of financial transactions in the context of suspicious activities will avoid conflicts of meaning in the context of lex superior derogat legi inferiori and will provide the ability to the reporting party to carry out legal obligations and moral obligations for the effectiveness of the anti-money laundering regime in Indonesia.